VIP Modulation of Hippocampal Synaptic Plasticity: A Role for VIP Receptors as Therapeutic Targets in Cognitive Decline and Mesial Temporal Lobe Epilepsy - Cunha-Reis, Diana; Caulino-Rocha, Ana (Frontiers in Cellular Neuroscience, 2020)
Vasoactive intestinal peptide (VIP) is an important modulatory peptide throughout the CNS acting as a neurotransmitter, neurotrophic or neuroprotective factor. In the hippocampus, a brain area implicated in learning and memory processes, VIP has a crucial role in the control of GABAergic transmission and pyramidal cell activity in response to specific network activity by either VIP-containing basket cells or interneuron-selective (IS) interneurons and this appears to have a differential impact in hippocampal-dependent cognition. At the cellular level, VIP regulates synaptic transmission by either promoting disinhibition, through activation of VPAC1 receptors, or enhancing pyramidal cell excitability, through activation of VPAC2 receptors. These actions also control several important synaptic plasticity phenomena such as long-term potentiation (LTP) and long-term depression (LTD). This paper reviews the current knowledge on the activation and multiple functions of VIP expressing cells in the hippocampus and their role in controlling synaptic transmission, synaptic plasticity and learning and memory processes, discussing also the role of VPAC1 and VPAC2 VIP receptors in the regulation of these different processes. Furthermore, we address the current knowledge regarding changes in VIP mediated neurotransmission in epileptogenesis and mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS), and discuss the therapeutic opportunities of using selective VIP receptor ligands to prevent epileptogenesis and cognitive decline in MTLE-HS.